Potential molecular mechanisms underlying muscle fatigue mediated by reactive oxygen and nitrogen species - Debold, Edward (Frontiers in Physiology, 2015)
Intense contractile activity causes a dramatic decline in the force and velocity generating capacity of skeletal muscle within a few minutes, a phenomenon that characterizes fatigue. Much of the research effort has focused on how elevated levels of the metabolites of ATP hydrolysis might inhibit the function of the contractile proteins. However there is now growing evidence that elevated levels of reactive oxygen and nitrogen species (ROS/RNS), which also accumulate in the myoplasm during fatigue, also play a causative role in this type of fatigue. The most compelling evidence comes from observations demonstrating that pre-treatment of intact muscle with a ROS scavenger can significantly attenuate the development of fatigue. A clear advantage of this line of inquiry is that the molecular targets and protein modifications of some of the ROS scavengers are well-characterized enabling researchers to begin to identify potential regions and even specific amino acid residues modified during fatigue. Combining this knowledge with assessments of contractile properties from the whole muscle level down to the dynamic motions within specific contractile proteins enable the linking of the structural modifications to the functional impacts, using advanced chemical and biophysical techniques. Based on this approach at least two areas are beginning emerge as potentially important sites, the regulatory protein troponin and the actin binding region of myosin. This review highlights some of these recent efforts which have the potential to offer uniquely precise information on the underlying molecular basis of fatigue. This work may also have implications beyond muscle fatigue as ROS/RNS mediated protein modifications are also thought to play a role in the loss of muscle function with aging and in some acute pathologies like cardiac arrest and ischemia.